A new ocotillol-type ginsenoside from stems and leaves of Panax quinquefolium L. and its anti-oxidative effect on hydrogen peroxide exposed A549 cells. Issue 17 (1st September 2020) - Qi, Zeng; Wang, Zhenzhou; Zhou, Baisong; Fu, Shuilian; Hong, Tie; Li, Pingya; Liu, Jinping
Abstract: A new ocotillol-type ginsenoside, namely 12-one-pseudoginsenoside F11 (12-one-PF11 ), was isolated from stems and leaves of Panax quinquefolium, whose structure was elucidated 6- O -[ α -L-rhamnopyranosyl-(1-2)- β -D-glucopyranosyl]-dammar-12-one-20S, 24R-epoxy-3 β, 6 α, 25-triol. 12-one-PF11 significantly suppressed hydrogen peroxide induced oxidative stress in human lung carcinoma A549 cells. As compared with model group, 12-one-PF11 improved cell viability of A549 cells in a dose-dependent manner, and significantly decreased the generation of malondialdehyde (MDA) and increased production of superoxide dismutase (SOD) and glutathione (GSH) and protein expression levels of nuclear related factor 2 (Nrf2) and heme oxygenase-1 (HO-1) in A549 cells. Graphical Abstract: